British Politics and European Elections 2004 - Butler, D. author. aut Link
XIV, 230 p.
Keywords: A 'non-election' in terms of popular perception, the 2004 European elections in the United Kingdom nevertheless provided a fascinating snapshot of the new, far more fluid electoral trends that have been emerging since the end of the Thatcher era, with Green, Eurosceptical, regional and single issue parties all jostling for electoral space with the bigger three. Like its predecessors, this book documents the background, framework and party preparations; recounts how the campaign unfolded; analyses the results and explores the consequences of the elections in both the British and the European context.